Marketing Communications - Fill, Chris; Turnbull, Sarah (Pearson International Content, 2023)
Get a solid grasp of the methods, processes, and issues surrounding marketing communications and develop your career with an industry-leading text that blends theory with contemporary marketing practice. Marketing Communications, 9th edition by Fill and Turnbull is the leading text that introduces you to the key topics of the subject. Ideal for undergraduate and postgraduate students in Marketing and related fields, this textbook guides you through the processes and actions of engaging audiences with brands, products, and services, from theory to practice. From introducing the subject and setting learning expectations to analysing and interpreting consumer behaviour, this latest edition follows a clear, streamlined structure that focuses on the strategic and tactical aspects of how brands engage audiences. With an approachable style and language that is easy to understand, the text delivers a rich blend of academic and practitioner materials that will help you understand the complexities of marketing communications. The book includes examples of contemporary, innovative marketing practices drawn from some of the world's leading brands and agencies, allowing you to explore the theories and ideas and acquire critical insight into the marketing communications landscape. The plethora of useful features and examples will encourage you to discuss and consider multiple interpretations around the major topics, providing you with the tools you need to develop your career in the field. Marketing Communications is recognised as the authoritative text for professional courses such as The Chartered Institute of Marketing and is supported by the Institute of Practitioners in Advertising.